Kebijakan Formulasi Hukum Pidana dalam Penanggulangan Tindak Pidana Korupsi - Ridwan Ridwan (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: Corruption has been increasing rapidly and destroying life of nation. It is not only making loss of state financial but also economic of people and becoming threat for national stability and international. This paper is going to answer the policy of corruption policy in the act applying now and in the future. This research applies juridical normative method by conceiving law as a norm that is a measure for human behavior by focusing on secondary data that are collected from primary data that are laws. Based on the research, it reveals that the policy of criminal law on preventing crime of corruption are facing some weakness hence the restoration is required by focusing on the element of making loss for the state. To consider its increase is to fast, hence the concept of Indonesian criminal code is understood as criminal law policy that is proper for suppressing corruption in the future. Criminal Law Policy Formula on Suppressing Corruption